PENERAPAN ISO 9126 SEBAGAI MEDIA PENINGKATAN KUALITAS DAN KEPERCAYAAN PEMINJAMAN DANA ONLINE PADA KREDIT XYZ - Muhamad Irsan; Sutan Mohammad Arif (Jurnal JI-Tech, 2021)
The objective to be achieved in this study is to create an android application that helps make it easier for people to borrow fund online. This application is an application that provides information about Online funds lending based on the Android OS Which includes borrowing funds, tenure, repair time. User can choose the loan amount to be selected with a low interest rate, then the desired results will appear in the creation and development of applications required by software, namely Java, Android, ADT, and Photoshop